Health‐related quality of life, uncertainty and coping strategies in solid organ transplant recipients during shielding for the COVID‐19 pandemic. (16th September 2021) - McKay, Siobhan C.; Lembach, Hanns; Hann, Angus; Okoth, Kelvin; Anderton, Joy; Nirantharakumar, Krishnarajah; Magill, Laura; Torlinska, Barbara; Armstrong, Matthew; Mascaro, Jorge; Inston, Nicholas; Pinkney, Thomas; et al.
Summary: Strict isolation of vulnerable individuals has been a strategy implemented by authorities to protect people from COVID‐19. Our objective was to investigate health‐related quality of life (HRQoL), uncertainty and coping behaviours in solid organ transplant (SOT) recipients during the COVID‐19 pandemic. A cross‐sectional survey of adult SOT recipients undergoing follow‐up at our institution was performed. Perceived health status, uncertainty and coping strategies were assessed using the EQ‐5D‐5L, Short‐form Mishel Uncertainty in Illness Scale (SF‐MUIS) and Brief Cope, respectively. Interactions with COVID‐19 risk perception, access to health care, demographic and clinical variables were assessed. The survey was completed by 826 of 3839 (21.5%) invited participants. Overall, low levels of uncertainty in illness were reported, and acceptance was the major coping strategy (92%). Coping by acceptance, feeling protected, self‐perceived susceptibility to COVID‐19 were associated with lower levels of uncertainty. Health status index scores were significantly lower for those with mental health illness, compromised access to health care, a perceived high risk of severe COVID‐19 infection and higher levels of uncertainty. A history of mental health illness, risk perceptions, restricted healthcare access, uncertainty and coping strategies was associated with poorer HRQoL in SOT recipients during strict isolation. These findings may allow identification of strategies to improve HRQoL in SOT recipients during the pandemic. Abstract : Solid organ transplant recipients are required to take additional precautions to protect themselves from COVID‐19. Perceived health status was significantly lower for those with mental health illness, compromised access to care and a self‐perceived risk of severe COVID‐19. Transplant centres should consider this in their service delivery.